Periodontitis and Sjogren's syndrome: a bidirectional two-sample mendelian randomization study - Yixuan Liu; Nuozhou Liu; Peiyan Sun; Yi Liu; Wei Hua (BMC, 2024)
Abstract Objectives Observational studies indicated a controversial relationship between periodontitis (PD) and Sjogren's syndrome (SS). To overcome restrictions in conventional observational studies, we conducted a two-sample Mendelian randomization (MR) analysis to assess the potential bidirectional relationship between PD and SS. Methods We utilized the largest available genome-wide association study (GWAS) of European ancestry on both PD (17,353 cases-28,210 controls) and SS (2495 cases-365,533 controls) for MR genetic instrument selection. The random-effect inverse-variance weighted (IVW) method complemented by Causal Analysis Using Summary Effect (CAUSE), weighted median, weighted mode, simple mode, MR-Egger regression, and MR-pleiotropy residual sum and outlier (MR-PRESSO) was used for MR analysis. Subsequent pleiotropy and heterogeneity tests were conducted. Results IVW analysis exhibited neither an effect of PD on SS (OR = 0.939, 95%CI = 0.525-1.677, P = 0.8304) nor that of SS on PD (OR = 1.007, 95%CI = 0.977-1.038, P = 0.6440). The other five complementary methods further recognized the null association with an effect size close to one. No significant pleiotropy was detected in the relationship between PD and SS (P > 0.05). Heterogeneity existed in the effect of PD on SS but not vice versa. Conclusions No genetic causality between PD and SS or vice versa was supported by our results under MR assumptions and limitations. The study results provided new insights into the relationship between periodontal status and sjogren's syndrome, highlighting the need for a more prudent medical intervention.